Do female weightlifters snatch differently? Analysis of barbell kinematics using statistical parametric mapping - Sandau, I.; Rudloff, A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to analyse gender differences in barbell kinematics of the snatch in international elite weightlifters. At the 2019 Senior World Championships, horizontal and vertical barbell kinematics of the 1RM snatch lifts of the top 5 female and male weightlifters of all 10 body weight categories were assessed using two-dimensional video analysis (50 Hz). Gender differences were analysed for kinematic time series data using statistical parametric mapping. Results revealed almost similar mean snatch barbell trajectory and velocity pattern for female compared to male weightlifters. Significant differences were detected during the 1st pull with lower barbell distance and velocity. However, the few sex differences may be attributed to the high variability of barbell kinematic parameters, which are due to the dependency on body weight.